Utilization of Glass Waste in Silica Gel Production Using Sodium Hydroxide (NaOH) with The Sol-Gel Method - Rahmawati, Belinda Tri Setya; Vidyantari, Lyra; Sumada, Ketut (Indonesian Journal of Chemical Research, 2025)
The utilization of glass waste as raw material for silica gel using the sol-gel method to produce high-quality products while reducing inorganic waste. Silica is extracted from glass waste using sodium hydroxide (NaOH), then converted into sodium silicate. Silica gel synthesis is carried out by varying two main parameters: the sodium silicate: water ratio (1:1, 1:2, 1:3, 1:4, and 1:5) and sulfuric acid concentration (1.5 M, 2 M, 2.5 M, 3 M, and 3.5 M). Product characterization was performed using XRF for SiO₂ content, XRD for amorphous structure, and BET for specific surface area. The highest SiO₂ content of 86.83% was obtained at a ratio of 1:5 and H₂SO₄ concentration of 3.5 M. In contrast, the highest specific surface area of 186.82 m²/g was achieved at the same ratio and 3 M. These conditions highlight the balance between sufficient acid strength to remove metallic and organic impurities and adequate dilution to maintain effective mass transfer, resulting in a SiO₂ purity of up to 99%. These results highlight the high potential of glass waste as an alternative silica source for adsorbent and catalyst support applications.